Study on the extremely large seismic ground motion amplification on weak-motion seismograms from the Gongquan valley - Zhou, Qiang; Yu, Jiashun; Han, Chao; Yuan, Jianlong; Fu, Xiaobo; Yu, Kun; Hou, Xiaoping; Fan, Xinran (Frontiers in Earth Science, 2025)
The Ms 6.0 Changning Earthquake in 2019 caused severe damage to Gongquan Town, Sichuan. Our on-site investigation of seismic damage found that the three-dimensional topography and geological conditions of the town may have exacerbated the earthquake’s amplification effects. Research on the amplification effects of seismic ground motion will be of help to understand the local seismic damage mechanisms and provide a scientific basis for disaster prevention and reduction in the region. To this end, we deployed a seismic array in Gongquan Town to observe seismic activities and analyze the amplification effects in the area. The research results, from weak-motion seismograms of aftershocks, indicate that there is a significant seismic ground motion amplification in Gongquan Town, with an average amplification factor of 11 over the frequency range of 5–7 Hz. Additionally, the amplification varied widely among different sites in different earthquakes, with Site G09 experiencing an amplification as high as 26 times of Site G06 during one of the earthquakes. Simulation studies suggest that the extreme amplification at G09 is not caused by the soil layers directly beneath the site. Further analysis found that the extreme amplification at this site is closely related to the orientation of the seismic source, with earthquakes north-northeast to G09 more likely to cause extreme seismic motion amplification at the site. The large peak amplification at G09 of weak motion data is likely to be significantly reduced in a large earthquake due to nonlinearity. However, the phenomenon reminds us to pay special attention to the risk of significant damage caused by the combined effects of extreme amplification in future earthquake defense efforts.